2001
DOI: 10.1002/path.1020
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of matrix glycoproteins in vascular calcification and fibrosis: an immunohistochemical study

Abstract: Calcification and fibrointimal proliferation are associated with advanced complicated atherosclerosis in large arteries but may also occur in smaller vessels, resulting in ischaemic tissue necrosis. This study investigates whether the mechanisms of calcification and intimal fibrosis are similar in vessels of different sizes. The localization of osteopontin (OPN), matrix Gla protein (MGP), thrombospondin‐1 (TSP‐1), and cartilage oligomeric matrix protein (COMP) was investigated in three types of human vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 30 publications
4
72
2
1
Order By: Relevance
“…However, fibrous-cap atheromatous lesions and fibrocalcific plaques express high levels of many of these proteins, particularly in regions of plaque where calcification is seen. Lamellar bone-like structures containing osteoblast-like cells may be found in association with matrix vesicles, and high expression of bone-matrix proteins in regions adjacent to mineralized plaque has been reported (19,30). Collectively, these findings support the concept that arterial calcification occurs in plaque microenvironments in a manner that recapitulates osteogenesis.…”
Section: Active Osteoblast-like Arterial Cell Modelsupporting
confidence: 74%
“…However, fibrous-cap atheromatous lesions and fibrocalcific plaques express high levels of many of these proteins, particularly in regions of plaque where calcification is seen. Lamellar bone-like structures containing osteoblast-like cells may be found in association with matrix vesicles, and high expression of bone-matrix proteins in regions adjacent to mineralized plaque has been reported (19,30). Collectively, these findings support the concept that arterial calcification occurs in plaque microenvironments in a manner that recapitulates osteogenesis.…”
Section: Active Osteoblast-like Arterial Cell Modelsupporting
confidence: 74%
“…Finally, pericytes may be involved in the development and progression of several pathological conditions, including vascular calcification. 30,31 Indeed, markers of both cartilage and bone have been identified in calcified blood vessels, [31][32][33][34][35] and it has been suggested that a subpopulation of SM cells that resemble pericytes (calcifying vascular cells) contributes to this calcification. 30 -32 A recent study has shown that these cells also have multilineage potential in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that evidence for similar expression patterns in calcified human arteries have recently been reported. Osteopontin levels were increased (25,26) and ␣ smooth muscle actin levels were decreased (25) in calcified medial layers of cutaneous blood vessels in patients with calcific uremic arteriolopathy. Furthermore, staining for osteopontin and other bone matrix molecules was strongly correlated with medial calcification in epigastric arteries of dialysis patients (27).…”
Section: Mechanistic Evidence For Hyperphosphatemiainduced Calcificationmentioning
confidence: 99%